Consistent resource base of a foreign subsidiary's greenfield expansion. Issue 1 (2014) - ,; ,
<x xml:space="preserve">Abstract</x> Purpose – The purpose is to extend the understanding of the resource base of the industrial firm's greenfield expansion on a foreign country market once a wholly owned subsidiary has been established. Design/methodology/approach – A conceptual framework is developed relying on the resource‐based theory of strategy. Resource bases in terms of value‐adding activities of four Swedish industrial firms' subsidiaries in the USA are analysed. Four theoretical propositions are formulated regarding consistent associations among the activities and contingencies that are relevant to expansion on a foreign country market. Findings – The propositions show how foreign subsidiaries' value‐adding activities are aligned with two contingencies: the corporate strategy manifested by the product/market knowledge transferred from the parent firm that enable local expansion and the subsidiary's knowledge of competition barriers that obstruct local expansion. The value‐adding activity may be basic or advanced and may repeat the parent firm's activity. Research limitations/implications – US subsidiaries of four Swedish industrial firms were analysed. The propositions may be turned into hypotheses suitable for tests in statistical studies. A test may include firms from different home countries and subsidiaries on different host country markets. Practical implications – The conceptual framework and the propositions provide a ground for an industrial firm's decision to conduct a strategy of greenfield expansion on a foreign country market once a wholly owned subsidiary has been established. Originality/value – The framework is unique and emphasizes that both knowledge stemming from corporate strategy and knowledge of local competition need to be acknowledged in order to understand firm's greenfield expansion on a foreign country market. <ack> <x xml:space="preserve">Acknowledgements</x> The authors are grateful for valuable comments received from reviewers of European Business Review. Sofie Farneman, Swedish‐American Chamber of Commerce, supported the search for case companies and Daniel Svanberg Nilsson took part in the collection of case information. The work was financially supported by Linnaeus University. </ack>